Key success factors and challenges that affect small-medium enterprises (SMEs) toward internationalization in Malaysia - Kam, Mei Jeng; Leong, Yu Kang (2019)
In current world globalisation, small-medium enterprises (SMEs) are moving toward internationalisation. SMEs had played a vital role in the country’s economic development where it improves the economic growth and industrial development in Malaysia’s economy. However, SMEs may confront rivalry from foreign competitors, may involve in worldwide supply chains, and be hoping to expand their market place internationally due to the effects of globalisation. In Budget 2019, the government is designing a development plan to assist SMEs to meet the business challenges in the competitive global business environment. This research draws the essential government support needed in assisting SMEs in Malaysia. These include marketing assistance, financial assistance and the competitive capabilities of the assistance in helping the SMEs to face the challenges in the competitive environment. Furthermore, this research also highlights the critical challenges of SMEs will be faced if they are moving toward internationalization.